PROSES PENYELESAIAN SOAL EKSPRESI ALJABAR PADA PESERTA DIDIK DI KELAS VII MTS HIDYATUL MUHSININ - Maryam Maryam; Edy Yusmin; Rustam Rustam (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
This study discusses the process of solving algebraic expressions inclass VII MTs Hidayatul Muhsinin. The method used is a qualitativedescriptive approach. Subjects in this study amounted to fifteenstudents. Data were collected using written tests and interviews.Data were analyzed using qualitative analysis techniques based onPolya stages. The results showed that, students at the stage ofunderstanding the problem expressed in writing, writing down theknown elements and the elements being asked, then at the stage ofmaking a written problem-solving plan, writing down the knownelements and the elements that were asked on the question. In thestage of implementing the completion plan, students still make manymistakes because of the lack of accuracy in the process of solvingalgebraic expression questions. At the last stage, students checkanswers. At the time of the interview, students were able tounderstand what variables, coefficients and constants were.